Jurysdykcja krajowa sądów polskich według umów zawartych przez Polskę z państwami europejskimi - Zedler, Feliks (Wydział Prawa i Administracji UAM, 1991)
The article presents the problems of domestic jurisdiction in civil cases, regulated in bilateral contracts signed by Poland with Austria, Bulgaria, Czecho-Slovakia, Finland, France, Jugoslavia, German Democratic Republic, Romania, Hungary and the USSR.
Domestic Jurisdiction of Polish courts according to contracts concluded by Poland with European countries